Pengembangan Media Pembelajaran MEBUPA (Mengenal Budaya Pamekasan) Berbasis Google Sites pada Pelajaran Pendidikan Pancasila Kelas V di SDN Polagan 1 - Innani Norlaili; Widya Trio Pangestu (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to develop MEBUPA (Introducing Pamekasan Culture) learning media based on Google Sites that is valid, effective, and attractive for the Pancasila Education subject, specifically on the topic of Introducing Pamekasan Culture, for fifth-grade students at SDN Polagan 1. The media was developed using the ADDIE model and incorporates learning materials in the form of text, images, audio, and videos. The validation results indicated that MEBUPA learning media had a very high level of validity, with assessment scores of 92.5% from the learning media expert, 92.5% from the subject matter expert, 87.5% from the instructional design expert, and 92.5% from the assessment expert. The effectiveness of the media was determined based on students' learning outcomes after using MEBUPA. The results of the Paired Sample t-test showed a significance value (Sig. (2-tailed)) of 0.001 < 0.05 in the small-group trial and 0.000 < 0.05 in the large-group trial. These findings indicate that MEBUPA learning media is effective for use in the learning process. The attractiveness of the media was assessed through teacher and student response questionnaires. In the small-group trial, the teacher response score reached 97.5%, while the student response score was 95.5%. In the large-group trial, the teacher response score was 97.5%, and the student response score reached 96.5%. These results indicate that MEBUPA learning media falls into the very attractive category. Based on the findings of this study, it can be concluded that MEBUPA learning media based on Google Sites is valid, effective, and attractive for use in Pancasila Education learning on the topic of Introducing Pamekasan Culture for fifth-grade students at SDN Polagan 1.